Silicon carbon material, preparation method thereof and lithium ion battery
By co-deposition of silicon lithium and doping of organic lithium gas on porous carbon, the problems of low lithium content and serious silicon expansion in existing silicon carbon materials are solved, and the high capacity, excellent circulation and rate performance of lithium-ion batteries are achieved.
Patent Information
- Application Number
- CN202411853668.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The lithium content in existing silicon-carbon materials is low and the volume expansion of silicon is severe, resulting in poor rate performance, first-effect and cycle performance of lithium-ion batteries.
By co-deposition of silicon lithium on porous carbon, the small atomic radius of lithium is used to preferentially embed in the ultramicro pores, reducing the fill degree of silicon and increasing the lithium content, while improving the conductivity of silicon carbon materials and the embedded efficiency of lithium are improved by doping organic lithium gas.
It significantly improves the lithium content in silicon-carbon materials, reduces the expansion of silicon, and improves the capacity, rate performance, cycle performance and first-time effect of lithium-ion batteries.
Smart Images

Figure CN119683602A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a silicon-carbon material and a preparation method thereof, and a lithium-ion battery. Background Art
[0002] Silicon-carbon anode material is one of the most popular technologies for improving battery density today. 15 Si4 calculation, its energy density can reach about 3500mAh / g, however, in the process of use, limited by the immaturity of the preparation process and the inherent properties of the lithium insertion and delithiation mechanism, the volume expansion of silicon in the silicon-carbon material is serious, the rate performance and initial efficiency of the battery are low, these reasons lead to its limited application. At present, it is mainly used in 3C digital products with relatively low rate requirements, mainly in the field of mobile phones and tablets, mainly because it does not have high requirements for rate performance. In the silicon-carbon negative electrode material with only 10% added, its rate performance is often only about 3C. In the existing technology, although the double-layer coating technology, laser drilling technology, low binder formulation technology, fast charging electrolyte technology, etc. can improve the rate to 4C to a certain extent, it is still impossible to take into account both excellent rate performance and first efficiency. In order to further reduce the volume expansion of silicon and further improve the first efficiency, the existing technology only pre-lithiumizes the porous carbon by doping lithium salts before depositing silicon, and then deposits silicon. Although the lithium content is increased and the first efficiency of the lithium-ion battery is improved, the lithium content of the obtained silicon-carbon material is still low, and the first efficiency of the lithium-ion battery is still poor, and it is still impossible to take into account both excellent rate performance and excellent cycle performance and capacity performance. Summary of the invention
[0003] In order to solve the defects of low lithium content and severe volume expansion of silicon in existing silicon-carbon materials, the present invention provides a silicon-carbon material and a preparation method thereof, and a lithium-ion battery. The obtained silicon-carbon material has a high content of lithium and can greatly reduce the expansion of silicon. When the silicon-carbon material is used as a negative electrode material in a lithium-ion battery, the obtained lithium-ion battery has excellent capacity performance and can also take into account excellent cycle performance, rate performance and first efficiency.
[0004] In order to achieve the above technical objectives, the present invention adopts the following technical solutions.
[0005] The present invention provides a method for preparing a silicon-carbon material, which comprises the following steps:
[0006] S1, performing a first vapor deposition on porous carbon to obtain a silicon-carbon material precursor;
[0007] Wherein, the first vapor deposition is silicon-lithium co-deposition, the first deposition gas comprises a silicon source gas and a lithium source gas, and the silicon source gas and the lithium source gas are introduced simultaneously;
[0008] S2, performing a second vapor deposition on the silicon-carbon material precursor to obtain the silicon-carbon material;
[0009] Wherein, the second vapor deposition is carbon deposition, and the second deposition gas includes a carbon source gas.
[0010] In the present invention, in step S1, the first vapor deposition is silicon-lithium co-deposition considering that the porous carbon contains ultra-micropores and oxygen-containing functional groups, which will lead to irreversible release and embedding of lithium ions in the battery. It is generally believed that the filling degree of ultra-micropores is the key to the expansion of the silicon-carbon negative electrode. By reducing the filling degree of silicon in the ultra-micropores, the expansion of the silicon-carbon negative electrode can be reduced. Based on the Knudsen flow principle of silane deposition, because the atomic radius of lithium is smaller, lithium will be preferentially embedded in these gaps through the doping of lithium atoms. These embedded lithiums reduce the secondary embedding of silicon atoms, reduce the filling degree of silicon in the ultra-micropores, and reduce the expansion caused by the original simple deposition of silicon embedded in lithium. At the same time, because the oxygen polarity in the oxygen-containing functional groups of porous carbon is stronger, when lithium is embedded, lithium can preferentially react with the oxygen therein to generate inorganic solid electrolytes such as Li-O and Li-N. It is generally believed that these inorganic solid electrolytes have excellent ion diffusion channels, thereby improving the shuttling ability of lithium ions. In addition, when lithium atoms are embedded in the silicon deposition process, because the conductivity of lithium is better than that of pure silicon, silicon-lithium co-deposition helps to reduce the partial pressure of silicon-carbon materials, further improving the rate performance and capacity performance. At the same time, lithium doping expands the lattice fringes in silicon nanoparticles, making the silicon nanoparticles disordered, which is also conducive to improving the rate performance.
[0011] In step S1, the lithium source gas preferably includes organic lithium gas and / or inorganic lithium gas, and more preferably includes organic lithium gas. The inorganic lithium gas refers to a gas formed by lithium vapor and an inorganic compound containing lithium, and the organic lithium gas refers to a gas formed by an organic compound containing lithium.
[0012] The organic lithium gas is preferably a nitrogen-containing organic lithium gas; the organic lithium gas is, for example, an amide lithium gas or a phenyl lithium gas.
[0013] Wherein, the inorganic lithium gas is preferably lithium vapor.
[0014] In the present invention, in step S1, when the lithium source gas is a nitrogen-containing organic lithium gas, nitrogen atoms will be doped into the silicon nanoparticles, reducing the bandgap of the silicon nanoparticles, thereby improving their conductivity, which can reduce the partial pressure of the internal resistance of the battery, thereby improving the rate performance and capacity performance of the battery. The joint implementation of nitrogen doping and silicon-lithium co-deposition can significantly reduce the DC resistance of the silicon-carbon material and further improve the rate performance of the battery.
[0015] In step S1, the difference between the cracking temperatures of the lithium source gas and the silicon source gas is preferably 300°C or less.
[0016] In step S1, the silicon source gas may be a silicon source gas conventionally used in vapor deposition in the art, preferably including silane. The silane is preferably monosilane and / or disilane.
[0017] In some preferred embodiments, in step S1, the first deposition gas includes silane and organic lithium gas.
[0018] In some specific embodiments, in step S1, the first deposition gas includes monosilane and lithium amide.
[0019] In some specific embodiments, in step S1, the first deposition gas includes monosilane and phenyllithium.
[0020] In some specific embodiments, in step S1, the first deposition gas includes disilane and lithium amide.
[0021] In some preferred embodiments, in step S1, the first deposition gas includes silane and inorganic lithium gas.
[0022] In some specific embodiments, in step S1, the first deposition gas includes monosilane and lithium vapor.
[0023] In step S1, the lithium source gas is preferably formed by heating a lithium source.
[0024] The absolute pressure P1 of the heating treatment is preferably 30-70 kPa, such as 63 kPa.
[0025] The temperature T1 of the heating treatment is preferably 300-500° C., for example, 360° C. At the above preferred heating treatment temperature, lithium amide can be prevented from decomposing prematurely and lithium amide can be ensured to form lithium amide gas.
[0026] In step S1, before the first deposition gas is introduced, preferably, the environment in which the first deposition gas is located is maintained at an absolute pressure P2 of 25-60 kPa, for example, 52 kPa.
[0027] In step S1, before the first deposition gas is introduced, preferably, the environment in which the first deposition gas is located is maintained at a temperature T2 of 300-500°C, for example, 380°C.
[0028] In step S1, the temperature T3 of the first vapor deposition is preferably 400-800°C, for example 550°C.
[0029] In step S1, the time of the first vapor deposition is preferably 1-100 min, for example, 5 min.
[0030] In step S1, the absolute pressure P3 of the first vapor deposition is preferably 10-50 kPa, for example, 42 kPa.
[0031] Preferably, in step S1, the first vapor deposition satisfies: T1<T2<T3, and P1>P2>P3. Under the above conditions, it can be ensured that the first deposition gas does not adhere to the wall and can maintain the gas form.
[0032] In step S1, the first deposition gas preferably also includes a protective gas, such as one or more of nitrogen, helium and argon; wherein the volume ratio of the protective gas to the silicon source gas is preferably (3-5): 1, such as 4: 1. Preferably, the protective gas and the silicon source gas are introduced in the form of a mixed gas.
[0033] In step S1, the flow rate of the silicon source gas is preferably 0.5-5 L·kg -1 ·min -1 , for example 2L·kg -1 ·min -1 Among them, "L·kg -1 ·min -1 ” refers to the volume of the silicon source gas introduced into the porous carbon per unit mass per minute.
[0034] In step S1, the flow rate of the lithium source gas is preferably 5-500 mg·kg -1 ·min -1 , more preferably 5-250 mg·kg -1 ·min -1 , for example 7 mg kg -1 ·min -1 , 14mg·kg -1 ·min -1 , 23mg·kg -1 ·min -1 , 28mg·kg -1 ·min -1 , 42mg·kg -1 ·min -1 , 46mg·kg -1 ·min -1 , 56mg·kg -1 ·min -1 , 70mg·kg -1 ·min -1 , 84mg·kg -1 ·min -1, 92mg·kg -1 ·min -1 , 118mg·kg -1 ·min -1 , 184mg·kg -1 ·min -1 or 230 mg kg -1 ·min -1 Among them, "mg·kg -1 ·min -1 ” refers to the mass of the lithium source gas introduced into the porous carbon per unit mass per minute.
[0035] In step S2, the temperature of the second vapor deposition may be the temperature conventionally used for carbon deposition in the art, preferably 400-800°C, for example 600°C.
[0036] And / or, in step S2, the time of the second vapor deposition is preferably 5-15 hours, for example 10 hours.
[0037] And / or, in step S2, the flow rate of the second deposition gas is preferably 0.5-5 L·kg -1 ·min -1 , for example 2L·kg -1 ·min -1 Among them, "L·kg -1 ·min -1 ” refers to the volume of the second deposition gas introduced into the porous carbon per unit mass per minute.
[0038] And / or, in step S2, the carbon source gas may be a carbon source gas conventionally used for carbon deposition in the art, preferably including one or more of alkynes, alkanes, olefins, aromatic compounds and carbohydrates, such as acetylene.
[0039] And / or, in step S2, the second deposition gas further comprises a protective gas, such as one or more of nitrogen, helium and argon. Preferably, in the second deposition gas, the volume ratio of the carbon source gas to the protective gas is preferably (3-5):1, for example, 4:1. Preferably, the protective gas and the carbon source gas are introduced in the form of a mixed gas.
[0040] Preferably, the preparation method of the silicon-carbon material is carried out in a vapor deposition device, which includes a gas generator, a mixer and a reaction furnace; the gas generator is provided with a first gas outlet, the mixer includes a first gas inlet, a second gas inlet and a deposition gas outlet arranged at different positions, the reaction furnace is provided with a deposition gas inlet, the first gas outlet of the gas generator is communicated with the first gas inlet of the mixer, and the deposition gas outlet of the mixer is communicated with the deposition gas inlet of the reaction furnace;
[0041] In step S1, the gas generator is used to generate a lithium source gas, and the lithium source gas is sequentially introduced into the mixer through the first gas outlet and the first gas inlet of the mixer; the silicon source gas is introduced into the mixer through the second gas inlet; the mixer is used to mix the silicon source gas and the lithium source gas to form the first deposition gas; the first deposition gas is sequentially introduced into the reactor through the deposition gas outlet of the mixer and the deposition gas inlet of the reactor; the porous carbon is subjected to a first vapor deposition in the reactor;
[0042] In step S2, the second deposition gas is introduced into the mixer through the second gas inlet, and then enters the reaction furnace through the deposition gas outlet of the mixer and the deposition gas inlet of the reaction furnace in sequence, and the silicon-carbon material precursor is subjected to a second vapor deposition in the reaction furnace.
[0043] In some embodiments, in step S1, the porous carbon satisfies one or more of the following conditions: ① The specific surface area is 1500-2500m 2 / g, ② the pore volume of micropores and ultramicropores accounts for 80-98%, ③ the pore volume of ultramicropores accounts for 0-25%, ④ the pore volume of mesopores and above accounts for 2-20%, ⑤ the pore volume is 0.7-1.4cm 3 / g, wherein the pore volume ratio refers to the volume percentage of the total pore volume of the porous carbon.
[0044] In some specific embodiments, the porous carbon satisfies one or more of the following conditions: ① The specific surface area is 1890 m 2 / g, ② the pore volume of micropores and ultramicropores accounts for 85.3%, ③ the pore volume of ultramicropores accounts for 17.3%, ④ the pore volume of mesopores and above accounts for 14.7%, and ⑤ the pore volume is 1.32cm 3 / g.
[0045] In the present invention, the porous carbon can be prepared by conventional methods in the art. The carbon source of the porous carbon can include one or more of resin, sucrose, glucose, fructose, starch, cellulose, triglyceride, fatty acid, hemicellulose, lignin and asphalt, preferably resin, more preferably phenolic resin.
[0046] In some embodiments, the porous carbon is prepared using phenolic resin as a carbon source.
[0047] In some specific embodiments, the method for preparing porous carbon comprises the following steps:
[0048] (1) spray drying a slurry containing a phenolic resin to obtain a carbon material precursor;
[0049] (2) carbonizing the carbon material precursor to obtain a porous carbon precursor;
[0050] (3) Activating the porous carbon precursor to obtain porous carbon.
[0051] In step (1), the slurry may further include a curing agent and a solvent; the curing agent is, for example, hexamethylenetetramine, and the solvent is, for example, ethanol. The mass ratio of the phenolic resin to the curing agent is preferably 100:(1-20), for example, 100:6.
[0052] In step (1), the spray drying temperature is preferably 90-180°C, for example 130°C.
[0053] In step (1), the spray drying is preferably performed to a particle diameter of 4-20 μm, for example 8 μm.
[0054] In step (2), the carbonization method may be a conventional carbonization method in the art, such as a staged heat treatment; preferably, the carbonization includes the following stages:
[0055] The first stage: heat up to 150-250℃ at 1-10℃ / min, keep warm for 50-180min;
[0056] The second stage: heat up to 600-700℃ at 1-10℃ / min and keep warm for 50-180min.
[0057] In some specific embodiments, the carbonization comprises the following stages:
[0058] The first stage: heating to 200℃ at a heating rate of 4℃ / min and keeping the temperature for 60min;
[0059] The second stage: heat up to 652°C at a heating rate of 4°C / min and keep warm for 60 minutes.
[0060] In step (2), the carbonization may be performed under an inert atmosphere, and the inert atmosphere preferably comprises one or more of nitrogen, helium and argon.
[0061] In step (3), the activation method can be a conventional activation pore-forming method in the art, such as alkali activation or gas activation, preferably gas activation.
[0062] The gas activation is preferably carbon dioxide activation or water vapor activation.
[0063] The ventilation volume of the gas activation is preferably 10-50 L·kg -1 ·min -1 , for example 2·L·kg -1 ·min -1 .
[0064] The gas activation temperature is preferably 450-800°C, for example 550°C.
[0065] The gas activation time is preferably 5-15 hours, for example 9 hours.
[0066] The present invention provides a silicon-carbon material, which is prepared by the method for preparing the silicon-carbon material as described above.
[0067] In the present invention, the silicon-carbon material may include a core-shell structure, the core-shell structure includes a core and an outer shell, the core includes porous carbon and a lithium-containing silicon layer; the lithium-containing silicon layer is arranged on the surface and in the pores of the porous carbon; the outer shell includes a carbon layer, and the carbon layer is coated on the surface of the core. The carbon layer coated on the surface of the core is not limited to the surface of the core. When the porous carbon also contains pores, the carbon layer can also be arranged in the pores of the porous carbon and coated on the surface of the lithium-containing silicon layer.
[0068] In the present invention, the lithium element in the lithium-containing silicon layer exists in the form of LiC6, lithium-containing nitride and / or silicon-lithium alloy.
[0069] In the present invention, the silicon element in the lithium-containing silicon layer exists in the form of silicon nanoparticles, silicon oxides and / or silicon-lithium alloys.
[0070] Preferably, the lithium content of the silicon-carbon material is 0.9%-8%, for example, 0.94%, 0.95%, 0.98%, 1.85%, 1.90%, 3.45%, 3.65%, 4.40%, 5.10%, 5.45%, 6.30%, 6.55% or 7.75%, where the percentage is the mass percentage of the silicon-carbon material.
[0071] Preferably, the silicon content of the silicon-carbon material is 45%-55%, for example, 47%, 49.72%, 50.39%, 50.79%, 51.45%, 51.34%, 51.64%, 51.69%, 51.75%, 52.66%, 53.06%, 53.12%, 53.13% or 53.14%, where the percentage is the mass percentage of the silicon-carbon material.
[0072] Preferably, the carbon content of the silicon-carbon material is 40%-55%, more preferably 42%-46%, for example, 42.53%, 42.91%, 43.06%, 43.21%, 43.45%, 43.96%, 44.6%, 44.86%, 45.04%, 45.49%, 45.91%, 45.93% or 52.02%, where the percentage is the mass percentage of the silicon-carbon material.
[0073] Preferably, the nitrogen content of the silicon-carbon material is 30-310 ppm, for example, 32 ppm, 33 ppm, 65 ppm, 132 ppm, 221 ppm, 290 ppm or 303 ppm.
[0074] Preferably, the powder conductivity of the silicon-carbon material is 13%-63%, for example, 13.2%, 22.2%, 24.1%, 25.3%, 25.2%, 29.4%, 26.2%, 37.3%, 40.9%, 44.2%, 49.6%, 59.3% or 62.1%.
[0075] Preferably, the Dv50 particle size of the silicon-carbon material is 7-9 μm, for example, 7.2 μm, 7.7 μm, 7.8 μm, 7.9 μm, 8 μm, 8.1 μm, 8.3 μm, 8.5 μm or 8.7 μm.
[0076] Preferably, the specific surface area of the silicon-carbon material is 3-6 m 2 / g, for example, 3.4m 2 / g, 3.6m 2 / g, 3.8m 2 / g, 4m 2 / g, 4.1m 2 / g, 4.2m 2 / g, 4.3m 2 / g, 4.4m 2 / g, 5.1m 2 / g, 5.2m 2 / g, 5.3m 2 / g or 5.4m 2 / g.
[0077] The present invention provides a pole piece, which comprises the silicon-carbon material as described above.
[0078] The present invention provides an application of the silicon-carbon material as described above as a negative electrode material in a lithium-ion battery.
[0079] The present invention also provides a lithium ion battery, which comprises the silicon-carbon material as described above.
[0080] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0081] The reagents and raw materials used in the present invention are commercially available.
[0082] The positive and progressive effects of the present invention are:
[0083] (1) In the preparation method of the silicon-carbon material of the present invention, silicon-lithium co-deposition is used to greatly reduce the lithium insertion expansion of the electrode using the silicon-carbon material, and the expansion of the silicon-carbon material in a fully lithium-intercalated state can be greatly reduced. The prepared lithium-ion battery has excellent capacity performance and can also take into account excellent cycle performance, rate performance and first efficiency.
[0084] Furthermore, when nitrogen-containing organic lithium gas is used as the lithium source gas, the efficiency of lithium deposition in the silicon-carbon material can be improved by doping with nitrogen atoms, and the conductivity of the silicon-carbon material can be improved, thereby further improving the rate performance.
[0085] (2) The preparation method of the silicon-carbon material can be completed in a single step, which is simple to operate, highly efficient, and has extremely high potential for industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0086] Figure 1 This is a schematic diagram of the structure of the device used for the first vapor deposition in Example 1.
[0087] The reference numerals are as follows:
[0088] 1-gas generator; 2-mixer; 3-reaction furnace;
[0089] 101 - first gas inlet; 102 - second gas inlet; 103 - deposition gas outlet. DETAILED DESCRIPTION
[0090] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0091] In the following examples and comparative examples, the phenolic resin was purchased from Hubei Hengye Technology Co., Ltd., model 2135.
[0092] Example 1
[0093] 1. Preparation of porous carbon:
[0094] (1) 1 kg of phenolic resin, 2 kg of ethanol, and 60 g of hexamethylenetetramine (HMT) were mixed by a high-speed homogenizer at a speed of 2000 r / min for 60 min. The mixture was spray-dried at 130° C. until the Dv50 particle size was 8 μm.
[0095] (2) The spray-dried powder was placed in a rotary furnace for cross-linking at 10 r / min and then carbonized. The heating curve in the first stage was 4°C / min, and the temperature was raised to 200°C and kept for 1 hour. The main purpose was to cross-link the phenolic resin. The heating curve in the second stage was 4°C / min, and the temperature was raised to 652°C and kept for 1 hour. The flow rate of nitrogen atmosphere protection was 1 L kg -1 ·min -1 Among them, "L·kg -1 ·min -1 ” refers to the volume of nitrogen introduced into the spray-dried powder per unit mass per minute.
[0096] (3) Activation of carbon materials: Activated in a CO2 atmosphere for 9 h at a flow rate of 2 L kg -1 ·min -1 , the temperature in the furnace is 550℃, and porous carbon is obtained.
[0097] The specific parameters of the obtained porous carbon are as follows:
[0098] The specific surface area is 1890m 2 / g, micropore volume accounts for 85.3% (of which ultramicropore volume accounts for 17.3%), and mesopore volume accounts for 14.7%. The above percentages are the volume percentages of the total pore volume of the porous carbon obtained. The pore volume is 1.32cm 3 / g.
[0099] 2. Preparation of silicon-carbon materials
[0100] The preparation method of silicon carbon material is in a vapor deposition device (schematic diagram as shown in FIG. Figure 1 ), the vapor deposition device includes a gas generator 1, a mixer 2 and a reaction furnace 3; the gas generator 1 is provided with a first gas outlet, the mixer 2 includes a first gas inlet 101, a second gas inlet 102 and a deposition gas outlet 103 arranged at different positions, the reaction furnace 3 is provided with a deposition gas inlet, the first gas outlet of the gas generator 1 is connected to the first gas inlet 101 of the mixer 2, and the deposition gas outlet 103 of the mixer 2 is connected to the deposition gas inlet of the reaction furnace 3.
[0101] S1. Performing the first vapor deposition to prepare a silicon-carbon precursor (silicon-lithium co-deposition):
[0102] Lithium amide is placed in a gas generator at a temperature of 360°C and an absolute pressure of 63 kPa, so that lithium amide is converted into lithium amide gas and heated at 23 mg kg -1 ·min -1 The flow rate is passed through the first gas outlet and the first gas inlet of the mixer into the mixer at 380°C and an absolute pressure of 52 kPa; monosilane gas and argon gas (volume ratio of 20:80, flow rate of 2 L·kg -1 ·min -1 ) is introduced into the mixer through the second gas inlet; the monosilane gas, argon gas and lithium amide gas are evenly mixed in the mixer to form a first deposition gas, and the first deposition gas is introduced into the reaction furnace (the absolute pressure is 42 kPa, the temperature is 550°C) through the deposition gas outlet of the mixer and the deposition gas inlet of the reaction furnace, and the porous carbon (165 g) placed in the reaction furnace is subjected to the first vapor deposition (absolute pressure is 42 kPa, temperature is 550°C, time is 8h) to obtain a silicon-carbon precursor.
[0103] S2, perform the second vapor deposition
[0104] The acetylene gas is introduced into the mixer through the second gas inlet (temperature is 380°C, absolute pressure is 52kPa), and then enters the reactor through the deposition gas outlet of the mixer and the deposition gas inlet of the reactor in turn, and the silicon-carbon material precursor is subjected to the second vapor deposition in the reactor (absolute pressure is 42kPa, time is 600min, temperature is 600°C). The flow rate of acetylene is 2L·kg -1 ·min -1 .
[0105] Example 2
[0106] The difference between Example 2 and Example 1 is that in the preparation of the silicon-carbon material, when the first vapor deposition is performed, phenyl lithium is used to replace amide lithium, and the flow rate of phenyl lithium gas is 84 mg·kg -1 ·min -1 , the other conditions remain the same as in Example 1.
[0107] Example 3
[0108] The difference between Example 3 and Example 1 is that in the preparation of silicon-carbon material, when performing the first vapor deposition, disilane is used to replace monosilane, and the other conditions remain the same as in Example 1.
[0109] Example 4
[0110] The difference between Example 4 and Example 1 is that in the preparation of silicon-carbon material, when the first vapor deposition is performed, the flow rate of lithium amide gas is 46 mg·kg -1·min -1 , the other conditions remain the same as in Example 1.
[0111] Example 5
[0112] The difference between Example 5 and Example 1 is that in the preparation of silicon-carbon material, when the first vapor deposition is performed, the flow rate of lithium amide gas is 92 mg·kg -1 ·min -1 , the other conditions remain the same as in Example 1.
[0113] Example 6
[0114] The difference between Example 6 and Example 1 is that in the preparation of silicon-carbon material, when the first vapor deposition is performed, the flow rate of lithium amide gas is 118 mg·kg -1 ·min -1 , the other conditions remain the same as in Example 1.
[0115] Example 7
[0116] The difference between Example 7 and Example 1 is that in the preparation of silicon-carbon material, when the first vapor deposition is performed, the flow rate of lithium amide gas is 184 mg·kg -1 ·min -1 , the other conditions remain the same as in Example 1.
[0117] Example 8
[0118] The difference between Example 8 and Example 1 is that in the preparation of silicon-carbon material, when the first vapor deposition is performed, the flow rate of lithium amide gas is 230 mg·kg -1 ·min -1 , the other conditions remain the same as in Example 1.
[0119] Example 9
[0120] The difference between Example 9 and Example 1 is that in the preparation of the silicon-carbon material, when the first vapor deposition is performed, lithium is used to replace lithium amide, and the flow rate of lithium vapor gas is 7 mg·kg -1 ·min -1 , the other conditions remain the same as in Example 1.
[0121] Example 10
[0122] The difference between Example 10 and Example 9 is that in the preparation of the silicon-carbon material, when the first vapor deposition is performed, the flow rate of the lithium vapor gas is 14 mg·kg -1 ·min -1 , the other conditions remain the same as in Example 9.
[0123] Embodiment 11
[0124] The difference between Example 11 and Example 9 is that in the preparation of the silicon-carbon material, when the first vapor deposition is performed, the flow rate of the lithium vapor gas is 28 mg·kg -1 ·min -1 , the other conditions remain the same as in Example 9.
[0125] Example 12
[0126] The difference between Example 12 and Example 9 is that in the preparation of the silicon-carbon material, when the first vapor deposition is performed, the flow rate of the lithium vapor gas is 42 mg·kg -1 ·min -1 , the other conditions remain the same as in Example 9.
[0127] Example 13
[0128] The difference between Example 13 and Example 9 is that in the preparation of the silicon-carbon material, when the first vapor deposition is performed, the flow rate of the lithium vapor gas is 56 mg·kg -1 ·min -1 , the other conditions remain the same as in Example 9.
[0129] Embodiment 14
[0130] The difference between Example 14 and Example 9 is that in the preparation of the silicon-carbon material, when the first vapor deposition is performed, the flow rate of the lithium vapor gas is 70 mg·kg -1 ·min -1 , the other conditions remain the same as in Example 9.
[0131] Comparative Example 1
[0132] The difference between this comparative example and Example 1 is that, in the preparation of the silicon-carbon material, when the first vapor deposition is performed, lithium amide is not used, and the other conditions remain the same as those in Example 1.
[0133] Comparative Example 2
[0134] The difference between this comparative example and Example 9 is that in the preparation of the silicon-carbon material, when the first vapor deposition is performed, lithium vapor and monosilane are used for step-by-step deposition, and the other conditions are consistent with those of Example 9.
[0135] The specific steps of the first vapor deposition are as follows:
[0136] ① Lithium deposition:
[0137] Lithium metal (3.36 g) was placed in a gas generator at a temperature of 360°C and an absolute pressure of 63 kPa, and the lithium metal was converted into lithium vapor at 7 mg kg -1 ·min -1The flow rate is passed through the first gas outlet and the first gas inlet of the mixer into the mixer at 380°C and an absolute pressure of 52 kPa; helium (flow rate of 2 L·kg -1 ·min -1 ) is introduced into the mixer through the second gas inlet; the helium and lithium vapor are evenly mixed in the mixer to form a first deposition gas, and the first deposition gas is introduced into the reaction furnace (absolute pressure is 42 kPa, temperature is 700°C) through the deposition gas outlet of the mixer and the deposition gas inlet of the reaction furnace, and the porous carbon (165 g) placed in the reaction furnace is subjected to the first vapor deposition (absolute pressure is 42 kPa, temperature is 700°C, time is 10 h); after the first vapor deposition is completed, a mixed gas of argon and nitrogen (nitrogen 0.5 L kg -1 ·min -1 , argon 1.5L·kg -1 ·min -1 ) is introduced into the mixer through the second gas inlet, and after 3 hours, lithium-containing porous carbon is obtained.
[0138] ②Silicon deposition:
[0139] Monosilane gas and argon (volume ratio of 20:80, flow rate of 2L kg -1 ·min -1 ) is introduced into the mixer through the second gas inlet; the monosilane gas, argon gas and lithium amide gas are evenly mixed in the mixer to form a first deposition gas, and the first deposition gas is introduced into the reaction furnace (with an absolute pressure of 42 kPa and a temperature of 550°C) through the deposition gas outlet of the mixer and the deposition gas inlet of the reaction furnace, and the lithium-containing porous carbon placed in the reaction furnace is subjected to the first vapor deposition (with an absolute pressure of 42 kPa, a temperature of 550°C, and a time of 8h) to obtain a silicon-carbon precursor.
[0140] Comparative Example 3
[0141] The difference between this comparative example and Example 1 is that in the preparation of the silicon-carbon material, when the first vapor deposition is performed, a step-by-step deposition method of lithium amide gas and monosilane is adopted, and the other conditions remain the same as in Example 1.
[0142] The specific steps of the first vapor deposition are as follows:
[0143] ① Lithium deposition:
[0144] Lithium amide (11.04 g) was placed in a gas generator at a temperature of 360°C and an absolute pressure of 63 kPa, so that lithium amide was converted into lithium amide gas and heated at 23 mg kg -1 ·min -1The flow rate is passed through the first gas outlet and the first gas inlet of the mixer into the mixer at 380°C and an absolute pressure of 52 kPa; helium (flow rate of 2 L·kg -1 ·min -1 ) is introduced into the mixer through the second gas inlet; the helium and lithium amide gases are uniformly mixed in the mixer to form a first deposition gas, and the first deposition gas is introduced into the reaction furnace (absolute pressure is 42 kPa, temperature is 700°C) through the deposition gas outlet of the mixer and the deposition gas inlet of the reaction furnace, and the porous carbon (165 g) placed in the reaction furnace is subjected to the first vapor deposition (absolute pressure is 42 kPa, temperature is 700°C, time is 10 h); after the first vapor deposition is completed, a mixed gas of argon and nitrogen (nitrogen 0.5 L kg -1 ·min -1 , argon 1.5L·kg -1 ·min -1 ) is introduced into the mixer through the second gas inlet, and after 3 hours, lithium-containing porous carbon is obtained.
[0145] ②Silicon deposition:
[0146] Monosilane gas and argon (volume ratio of 20:80, flow rate of 2L kg -1 ·min -1 ) is introduced into the mixer through the second gas inlet; the monosilane gas, argon gas and lithium amide gas are evenly mixed in the mixer to form a first deposition gas, and the first deposition gas is introduced into the reaction furnace (with an absolute pressure of 42 kPa and a temperature of 550°C) through the deposition gas outlet of the mixer and the deposition gas inlet of the reaction furnace, and the lithium-containing porous carbon placed in the reaction furnace is subjected to the first vapor deposition (with an absolute pressure of 42 kPa, a temperature of 550°C, and a time of 8h) to obtain a silicon-carbon precursor.
[0147] Effect Example 1
[0148] The silicon-carbon materials obtained in Examples 1-14 and Comparative Examples 1-3 were subjected to relevant tests or calculations on Dv50 particle size, silicon content, lithium content, carbon content, nitrogen content, powder conductivity, specific surface area, theoretical pre-lithium rate and achievement rate. The specific test methods or calculation methods are as follows:
[0149] (1) Dv50 particle size: tested using a laser particle size analyzer.
[0150] (2) Content of silicon and lithium: The content of silicon and lithium in the powder of the negative electrode material layer was tested using an inductively coupled plasma spectrometer (ICP, Agilent, model: Agilent 5800).
[0151] (3) Carbon content: A high-frequency carbon-sulfur analyzer (model DK-606) was used to test the carbon content in the powder of the negative electrode material layer.
[0152] (4) Nitrogen content: The nitrogen content in the powder of the negative electrode material layer was tested using an oxygen, nitrogen and hydrogen analyzer (Horiba, Japan, model EMGA-830).
[0153] (5) Powder conductivity: A powder conductivity meter (model FT-8100) is used based on the four-probe test principle and the test standard is GB / T 1 552-1995. A known amount of porous carbon composite solid powder is used to compress the volume to a set pressure value or pressure under hydraulic power, and the conductivity of the solid powder is measured online.
[0154] (6) Specific surface area: tested using Bestec NT-8000.
[0155] (7) Theoretical pre-lithium rate (%) and achievement rate:
[0156] Theoretical pre-lithium rate (%) = the mass of lithium element in the lithium source gas used / the mass of silicon-carbon material × 100
[0157] Achievement rate = actual lithium content / theoretical lithium rate
[0158] The above test results are shown in Table 1.
[0159] Effect Example 2
[0160] Preparation of pole pieces and lithium-ion batteries
[0161] Preparation of negative electrode slurry and negative electrode sheet: The negative electrode formula is designed as CMC: PAA: SBR: SP: CNTs: silicon-carbon material: graphite = 0.5: 3.5: 0.5: 0.1: 0.1: 10: 85.3 (by mass ratio). The negative electrode slurry preparation process is graphite → CMC → silicon-carbon material → SP → CNTs. After dispersing for 3 hours with a planetary disperser at a rotation speed of 300 r / min and a revolution of 1000 r / min, 80% of deionized water is injected at one time, and dispersed at 500 r / min and 600 r / min for 1 hour. PAA is added and dispersed at a rotation speed of 500 r / min and a revolution of 500 r / min for 1 hour, 20% of deionized water is injected, and finally SBR is added and dispersed at a rotation speed of 300 r / min and a revolution of 300 r / min for 1 hour to obtain a negative electrode slurry (solid content of 40%). The current collector uses 8μm thick copper foil. The above negative electrode slurry is used to coat the current collector on both sides. The thickness of the active material coated on one side is 40μm, and the compaction density is 1.8g / cm 3 , where the coating speed is 40 cm / s, the baking temperature is 80°C, and the drying time is 400s.
[0162] Preparation of electrolyte: The electrolyte composition is as follows, by mass percentage: ethylene carbonate (EC) 10%, propylene carbonate (PC) 15%, diethyl carbonate (DEC) 20%, propyl propylene (PP) 30%, LiPF6 15%, fluoroethylene carbonate (FEC) 6%, propylene sulfite (PS) 2.5%, and lithium difluorooxalatoborate (LiODFB) 1.5%.
[0163] Half-cell assembly: The positive electrode uses the above single-piece negative electrode plate, the negative electrode uses a lithium sheet, and 0.5g of the above electrolyte is assembled into a CR2032 button battery, and the voltage serial port uses 0-1.5V. The entire battery is assembled in a glove box to avoid contact with air.
[0164] Effect Example 3
[0165] The first-cycle lithium insertion expansion and compaction density of the pole piece prepared in Example 2 were tested and calculated:
[0166] (1) Expansion of the first lithium insertion: (thickness of the electrode after saturated lithium insertion - thickness of the copper foil) / (thickness of the electrode without lithium insertion - thickness of the copper foil), and the compaction density is controlled at 1.8g / cm 3 .
[0167] The above test results are shown in Table 2.
[0168] (2) The compaction density test method is: punch the electrode into a unit circle, test the weight, subtract the copper foil weight, and divide by the thickness to obtain the compaction density.
[0169] Effect Example 4
[0170] The lithium ion battery prepared in Example 2 was tested or calculated for the following first efficiency, gram capacity, number of cycle failures, rate retention rate, and hot box cycle retention rate. The specific test method or calculation method is as follows:
[0171] (1) 0.8V first effect (%)
[0172] The CR2032 button battery prepared in Example 2 was discharged at a constant voltage at 0.1 V / h to 0.000 V, and then charged at 0.1 / h to 0.8 V. The charge and discharge capacity was recorded, and the initial effect was calculated as the lithium removal capacity / lithium insertion capacity.
[0173] (2) 0.1C 0.8V gram capacity, using Xinwei CT-4008Q-5V6A
[0174] A CR2032 button battery prepared in Effect Example 2 was discharged at a constant voltage at 0.1 V / h to 0.000 V, and then charged at 0.1 V / h to 0.8 V, and the charging capacity was recorded at 0.1 C. Another CR2032 button battery prepared in Effect Example 2 was subjected to a constant current charge and discharge test at 0.1 C, and the charging capacity was recorded. After being discharged to 0 V, it was charged to 0.8 V to obtain the capacity.
[0175] Among them, the gram capacity of 0.1C 0.8V = capacity / mass of active material in the electrode; among them, the mass of active material in the electrode = mass of silicon-carbon material + mass of graphite.
[0176] (3) Cycle failure number, measured using Xinwei CT-4008Q-5V6A
[0177] ①0.5C 0.8V cycle failure number (measured at 25℃ and 45℃ respectively)
[0178] A CR2032 button battery prepared in Example 2 was discharged at a constant voltage at 0.1 V / h to 0.000 V, and then charged at 0.1 V / h to 0.8 V, and the charging capacity of 0.5C was recorded.
[0179] Another CR2032 button battery prepared in Example 2 was subjected to a constant current charge and discharge test at 0.5C with a recorded charge capacity, and was repeatedly charged and discharged from 0V to 0.8V, and the discharge capacity was recorded. The test was terminated when the discharge capacity was 60% of the 0.5C 0.8V gram capacity, and the number of cycles was recorded, which was the 0.5C 0.8V cycle failure number.
[0180] ②1C 0.8V cycle failure number (measured at 25℃ and 45℃ respectively)
[0181] A CR2032 button battery prepared in Example 2 was discharged at a constant voltage at 0.1 V / h to 0.000 V, and then charged at 0.1 V / h to 0.8 V, and the charging capacity was recorded. Another CR2032 button battery prepared in Example 2 was subjected to a constant current charge and discharge test at 1C with the charging capacity recorded, and was repeatedly charged and discharged from 0V to 0.8V, and the discharge capacity was recorded. The test was terminated when the discharge capacity was 60% of the C 0.8V capacity, and the number of cycles was recorded.
[0182] (4) Rate retention rate
[0183] 1C / 0.5C retention rate at 25℃: 0.8V cycle failure number / 0.5C 0.8V cycle failure number at 25℃.
[0184] 1C / 0.5C retention rate at 45℃: 1C 0.8V cycle failure number / 0.5C 0.8V cycle failure number at 45℃.
[0185] (5) 0.5C hot box cycle retention rate
[0186] 0.5C hot box cycle retention rate: 0.5C 0.8V cycle failure number at 45℃ / 0.5C 0.8V cycle failure number at 25℃.
[0187] The above test results are shown in Table 2.
[0188] Table 1
[0189]
[0190]
[0191] Table 2
[0192]
[0193] Note: “ / ” in Table 1 means that the condition parameter is not involved in the specific experiment.
[0194] It can be seen from Table 1 and Table 2 that in Examples 1-14 of the present invention, by adopting silicon-lithium co-deposition and the preparation method of the silicon-carbon material of the present invention, the pre-lithiation rate can reach above 0.6, and the preparation method can effectively realize the pre-lithiation of the silicon-carbon material. The lithium content of the obtained silicon-carbon material can reach above 0.9%, the silicon content can reach above 47%, and the powder conductivity can reach above 22%. The first-cycle lithium-embedded expansion of the pole piece obtained by using the silicon-carbon material as the negative electrode material is less than 90%, and the compaction density is 1.80g / cm 3 , the lithium-ion battery obtained by using the silicon-carbon material as the negative electrode material has excellent capacity performance and can also take into account excellent cycle performance, rate performance and first efficiency. Specifically, the 0.1C 0.8V gram capacity can reach more than 1650mAh / g, and even more than 1900mAh / g; on this basis, the number of 0.5C 0.8V cycle failures at 25°C can reach more than 190 cycles, the number of 0.5C 0.8V cycle failures at 45°C can reach more than 130 cycles, the number of 1C 0.8V cycle failures at 25°C can reach more than 150 cycles, the number of 1C 0.8V cycle failures at 45°C can reach more than 100 cycles, the 1C / 0.5C retention rate at 25°C can reach more than 0.80, the 1C / 0.5C retention rate at 45°C can reach more than 0.70, the 0.5C hot box cycle retention rate can reach more than 0.60, and the 0.8V first efficiency can reach more than 76%.
[0195] Compared with Example 1, Comparative Example 1 does not use lithium source gas, but only uses silicon source gas for the first vapor phase deposition. The obtained silicon-carbon material has no pre-lithium, the powder resistivity is low, the first-cycle lithium insertion expansion of the obtained electrode is very high, the first efficiency of the lithium-ion battery is significantly deteriorated, and the number of cycle failures, rate retention rate and hot box cycle retention rate are all greatly reduced.
[0196] Compared with Example 9, Comparative Example 2 did not use silicon-lithium co-deposition, but first used lithium vapor to pre-lithiate porous carbon, and then deposited silicon. The lithium content in the obtained silicon-carbon material was low, lithium could not be effectively deposited, and the powder resistivity was poor. Although the first cycle lithium insertion expansion of the pole piece at 25°C was low, the number of cycle failures, rate retention rate and hot box cycle retention rate were good, the first efficiency of the lithium-ion battery deteriorated, and the 0.1C0.8V gram capacity deteriorated significantly.
[0197] Compared with Example 1, Comparative Example 3 did not use silicon-lithium co-deposition, but first used lithium amide to pre-lithiate porous carbon, and then deposited silicon. The lithium content in the obtained silicon-carbon material was low, lithium could not be effectively deposited, and the powder resistivity was poor. Although the first cycle lithium insertion expansion of the pole piece at 25°C was low, the 0.1C 0.8V gram capacity of the lithium-ion battery was significantly reduced, and the first efficiency, cycle failure number, rate retention rate and hot box cycle retention rate were significantly deteriorated.
[0198] Compared with the lithium vapor used as the lithium source gas in Examples 9-14, there are further advantages in using amino lithium gas in Examples 1 and Examples 3-8. As can be seen from Table 1, under the condition of high compaction density, when amino lithium pre-lithium is used, the pre-lithium achievement rate can be improved and the powder conductivity can be improved. The resulting lithium-ion battery has better cycle performance and rate performance. This may be because trace nitrogen atom doping can be achieved when amino lithium gas is used, so that the lithium content in the silicon-carbon negative electrode material under the same process as lithium metal pre-lithium is enhanced. This is mainly due to the adsorption effect of nitrogen atoms. The formation of Li-N compounds with high ion channels can reduce ion diffusion resistance and ohmic resistance. In addition, it is also an important reason to make silicon atoms disordered and broaden ion channels; in addition, it is also related to the strong electronegativity of N atoms. Even if it forms saturated covalent bonds with silicon atoms and lithium atoms, it has a tendency to adsorb electrons based on its strong electron adsorption effect, which is still conducive to the embedding of lithium ions into silicon atoms.
[0199] It can be seen from Table 2 that compared with Examples 9-14, the number of cycles in Comparative Example 1 is lower, while the number of cycles of the lithium-ion batteries obtained from the silicon-carbon materials subjected to pre-lithiation in Examples 9-14 is higher. This may be because pre-lithiation increases the pore volume filling degree, making the material more pressure-resistant and less expanding.
[0200] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.
Claims
1. A method for preparing a silicon-carbon material, characterized in that: It includes the following steps: S1, performing a first vapor deposition on porous carbon to obtain a silicon-carbon material precursor; Wherein, the first vapor deposition is silicon-lithium co-deposition, the first deposition gas comprises a silicon source gas and a lithium source gas, and the silicon source gas and the lithium source gas are introduced simultaneously; S2, performing a second vapor deposition on the silicon-carbon material precursor to obtain the silicon-carbon material; Wherein, the second vapor deposition is carbon deposition, and the second deposition gas includes a carbon source gas.
2. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S1, the lithium source gas includes organic lithium gas and / or inorganic lithium gas, preferably includes organic lithium gas; Wherein, the organic lithium gas is preferably a nitrogen-containing organic lithium gas; Wherein, the organic lithium gas is, for example, lithium amide gas or phenyl lithium gas; Wherein, the inorganic lithium gas is preferably lithium vapor; And / or, in step S1, the difference between the cracking temperatures of the lithium source gas and the silicon source gas is preferably 300° C. or less; And / or, in step S1, the silicon source gas includes silane; wherein the silane is preferably monosilane and / or disilane; Preferably, the first deposition gas comprises monosilane and lithium vapor; Preferably, the first deposition gas comprises monosilane and lithium amide; Preferably, the first deposition gas comprises monosilane and phenyllithium; Preferably, the first deposition gas comprises disilane and lithium amide.
3. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S1, the lithium source gas is formed by heating a lithium source; Wherein, the absolute pressure P1 of the heating treatment is preferably 30-70 kPa, for example 63 kPa; Wherein, the temperature T1 of the heating treatment is preferably 300-500°C, for example 360°C; And / or, in step S1, before the first deposition gas is introduced, the environment in which the first deposition gas is located is maintained at an absolute pressure P2 of 25-60 kPa, for example, 52 kPa; And / or, in step S1, before the first deposition gas is introduced, the environment in which the first deposition gas is located is maintained at a temperature T2 of 300-500° C., for example, 380° C.; and / or, the temperature T3 of the first vapor deposition is 400-800° C., for example, 550° C.; And / or, in step S1, the time of the first vapor deposition is 1-100 min, for example, 5 min; And / or, in step S1, the absolute pressure P3 of the first vapor deposition is 10-50 kPa, for example, 42 kPa; Preferably, in step S1, the first vapor deposition satisfies: T1<T2<T3, and P1>P2>P3.
4. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S1, the first deposition gas also includes a protective gas, such as one or more of nitrogen, helium and argon; Wherein, the volume ratio of the protective gas to the silicon source gas is preferably (3-5):1, for example, 4:1; Wherein, the protective gas and the silicon source gas are preferably introduced in the form of a mixed gas; And / or, in step S1, the flow rate of the silicon source gas is 0.5-5 L·kg -1 ·min -1 , for example 2L·kg -1 ·min -1 ; And / or, in step S1, the flow rate of the lithium source gas is 5-500 mg·kg -1 ·min -1 , preferably 5-250 mg·kg -1 ·min -1 , for example 7 mg kg -1 ·min -1 , 14mg·kg -1 ·min -1 , 23mg·kg -1 ·min -1 , 28mg·kg -1 ·min -1 , 42mg·kg -1 ·min -1 , 46mg·kg -1 ·min -1 , 56mg·kg -1 ·min -1 , 70mg·kg -1 ·min -1 , 84mg·kg -1 ·min -1 , 92mg·kg -1 ·min -1 , 118mg·kg -1 ·min -1 , 184mg·kg -1 ·min -1 or 230 mg kg -1 ·min -1 .
5. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S2, the temperature of the second vapor deposition is 400-800° C., for example, 600° C.; And / or, in step S2, the second vapor deposition time is 5-15 hours, for example, 8 hours; And / or, in step S2, the flow rate of the second deposition gas is 0.5-5 L·kg -1 ·min -1 , for example 2L·kg -1 ·min -1 ; and / or, in step S2, the carbon source gas includes one or more of alkynes, alkanes, olefins, aromatic compounds and carbohydrates, such as acetylene; And / or, in step S2, the second deposition gas further includes a protective gas, such as one or more of nitrogen, helium and argon; Preferably, the protective gas and the carbon source gas are introduced in the form of a mixed gas; Preferably, in the second deposition gas, the volume ratio of the carbon source gas to the protective gas is (3-5):1, for example, 4:
1.
6. The method for preparing the silicon-carbon material as claimed in claim 1, characterized in that: The preparation method of the silicon-carbon material is carried out in a vapor deposition device, which includes a gas generator, a mixer and a reaction furnace; the gas generator is provided with a first gas outlet, the mixer includes a first gas inlet, a second gas inlet and a deposition gas outlet arranged at different positions, the reaction furnace is provided with a deposition gas inlet, the first gas outlet of the gas generator is communicated with the first gas inlet of the mixer, and the deposition gas outlet of the mixer is communicated with the deposition gas inlet of the reaction furnace; In step S1, the gas generator is used to generate a lithium source gas, and the lithium source gas is sequentially introduced into the mixer through the first gas outlet and the first gas inlet of the mixer; the silicon source gas is introduced into the mixer through the second gas inlet; the mixer is used to mix the silicon source gas and the lithium source gas to form the first deposition gas; the first deposition gas is sequentially introduced into the reactor through the deposition gas outlet of the mixer and the deposition gas inlet of the reactor; the porous carbon is subjected to a first vapor deposition in the reactor; In step S2, the second deposition gas is introduced into the mixer through the second gas inlet, and then enters the reaction furnace through the deposition gas outlet of the mixer and the deposition gas inlet of the reaction furnace in sequence, and the silicon-carbon material precursor is subjected to a second vapor deposition in the reaction furnace.
7. A silicon-carbon material, characterized in that: The silicon-carbon material is prepared by the method for preparing the silicon-carbon material according to any one of claims 1 to 6.
8. The silicon-carbon material according to claim 7, characterized in that: It includes a core-shell structure, which includes an inner core and an outer shell, wherein the inner core includes porous carbon and a lithium-containing silicon layer; the lithium-containing silicon layer is arranged on the surface and in the pores of the porous carbon; the outer shell includes a carbon layer, and the carbon layer is coated on the surface of the inner core.
9. The silicon-carbon material according to claim 7, characterized in that: The lithium content of the silicon-carbon material is 0.9%-8%, for example, 0.94%, 0.95%, 0.98%, 1.85%, 1.90%, 3.45%, 3.65%, 4.40%, 5.10%, 5.45%, 6.30%, 6.55% or 7.75%; And / or, the silicon carbon material has a silicon content of 45%-55%, for example, 47%, 49.72%, 50.39%, 50.79%, 51.45%, 51.34%, 51.64%, 51.69%, 51.75%, 52.66%, 53.06%, 53.12%, 53.13% or 53.14%; And / or, the carbon content of the silicon-carbon material is 40%-55%, preferably 42%-46%, for example, 42.53%, 42.91%, 43.06%, 43.21%, 43.45%, 43.96%, 44.6%, 44.86%, 45.04%, 45.49%, 45.91%, 45.93% or 52.02%; And / or, the nitrogen content of the silicon-carbon material is 30-310 ppm, for example, 32 ppm, 33 ppm, 65 ppm, 132 ppm, 221 ppm, 290 ppm or 303 ppm; and / or, the powder conductivity of the silicon-carbon material is 13%-63%, for example, 13.2%, 22.2%, 24.1%, 25.3%, 25.2%, 29.4%, 26.2%, 37.3%, 40.9%, 44.2%, 49.6%, 59.3% or 62.1%; And / or, the Dv50 particle size of the silicon-carbon material is 7-9 μm, for example, 7.2 μm, 7.7 μm, 7.8 μm, 7.9 μm, 8 μm, 8.1 μm, 8.3 μm, 8.5 μm or 8.7 μm; And / or, the specific surface area of the silicon-carbon material is 3-6m 2 / g, for example, 3.4m 2 / g, 3.6m 2 / g, 3.8m 2 / g, 4m 2 / g, 4.1m 2 / g, 4.2m 2 / g, 4.3m 2 / g, 4.4m 2 / g, 5.1m 2 / g, 5.2m 2 / g, 5.3m 2 / g or 5.4m 2 / g.
10. A lithium ion battery, characterized in that: It comprises the silicon-carbon material as described in any one of claims 7-9.
Citation Information
Patent Citations
Carbon-coated pre-lithiated silicon-based composite material as well as preparation method and application thereof
CN117393723A
Porous Carbon Structure-Hosted Silicon Oxide (SiOx), Anode, Lithium-ion Battery, and Production Method
US20240347698A1
Cited By
Solid electrolyte coated silicon-carbon composite material as well as preparation method and application thereof
CN121282175A